Die Zukunft der Zeitschriften im internationalen Feld ‚Recht und Gesellschaft‘ - Guibentif, P. (Rechtswirklichkeit - Das Blog des Berliner Arbeitskreises Rechtswirklichkeit, 2019)
Reflection about the changes taking place in the world of academic journals, and the role of sociology of law in the analysis of these changes, and the design of scientific policies in answering to them.